Landing Population and Toxicity Assessment of Common Horseshoe Crabs (Arthropoda: Xiphosura) from South West of Sarawak - Noor Jawahir, A.Raman (Universiti Malaysia Sarawak (UNIMAS), 2019)
Tachypleus gigas and Carcinoscorpius rotundicauda are commonly found in Malaysian waters, with both species co-existing in sandy beach, sandy-muddy and mangrove habitats. Although horseshoe crabs have long existed and are frequently consumed actively by Sarawakians, scientific literature on the horseshoe crab still remains inadequate. Therefore, this study covers the documentation for the spatial trend of landing population, morphometrics and toxicity of horseshoe crabs in three habitats in the south west of Sarawak, and the temporal trend of landing horseshoe crabs in a sandy-muddy habitat in Pasir Putih Village (2014-2016). The spatial trend shows that a high density of T. gigas landing population was recorded in sandy-muddy (186.08 individuals/100 m2) and sandy beach (168.18 individuals/100 m2) habitats. Meanwhile, C. rotundicauda dominated the sandy-muddy habitat (11.78 individuals/100 m2). The pH of sediments, sorting coefficient, percentage of silt-clay and percentage of total organic matter affected the density of landing horseshoe crabs in the south west of Sarawak. BEST and Particle Component Analysis performed between the environmental and the individual numbers (using Primer v.6) supported the results of the spatial and temporal trends. Only the carapace width-body weight relationship of female C. rotundicauda from sandy muddy and mangrove habitats experienced isometric growth (b value=3.00). The temporal trend indicated that landing horseshoe crabs numbers on the intertidal area of Pasir Putih Village are influenced by certain environmental parameters (dissolved oxygen, mean of grain and sediment sorting). Pasir Putih Village is considered as non-favourable to the growth and health of both species as shown by the negative allometric growth in their length-weight relationship analysis with ‘b’ value ranging from -2.64 to 2.90. Both species demonstrate monogamous behaviour during spawning activity although C. rotundicauda indicated a male-skewed landing population. Carapace width measurement study revealed that horseshoe crabs appeared to be species with sexual dimorphism with adult females being larger and heavier compared to males. The tetrodotoxin (TTX) concentrations in tissues of both species were analysed and determined by using liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). For spatial trend, only male (n=4) and female (n=1) C. rotundicauda from sandy-muddy habitat contain a high TTX concentration in soft tissues (♂=48.70 MU/g, ♀=35.91 MU/g) and eggs (♀=19.33 MU/g), which is considered toxic for human. C. rotundicauda are considered as TTX-bearing organisms and the concentration of TTX in soft tissues of male C. rotundicauda is affected by their body mass index. A temporal study showed no TTX concentration was detected in C. rotundicauda. However, T. gigas from Pasir Putih Village was considered safe to be consumed during other months with caution since high TTX concentration was detected in soft tissues (♂=44.27 MU/g, ♀=69.10 MU/g) in August 2016 exceeded the regulatory limit for seafood (>10 MU/g). These documentations are important for better management and conservation of horseshoe crabs in Sarawak. In addition, data obtained in this study will act as guidelines for the authorities to create public awareness in avoiding food poisoning due to the consumption of horseshoe crabs in the future. A consistent study and the latest sampling methods are crucial for future research in the distribution of horseshoe crabs in Sarawak.